The impact of mergers and acquisitions on performance of firms: A pre- and post-TRIPS analysis of India's pharmaceutical industry - Indrani Chakraborty; Paul Kattuman (Asia and the Global Economy, 2023)
This study analyses the impact of mergers and acquisitions on performance of Indian pharmaceutical firms following the implementation of TRIPS in 1995. In order to identify adequately the effect of mergers, we investigate the impact on firm performance of the merged vis-a-vis the non-merged firms in the post-TRIPS period using difference-in-differences and propensity score matching approaches. Our results suggest that firm performance improved in merged firms, following the mergers. We argue that our finding represents the incidence of “positioning” merger (Gorton et al., 2009). Moreover, transfer of technologies and capabilities helped to improve firm performance in merged firms. Our findings have significant policy implications for Asian countries.